Innovation and Digital Transformation PT. Kereta Api Indonesia (Persero) Tbk Its Implications on Company Performance - Natasya Ayu Andira; Henri Dwi Wahyudi (IECON: International Economics and Business Conference, 2023)
The purpose of this study is to determine the readiness of PT. Kereta Api Indonesia (PERSERO) Tbk in embracing digital business innovation and transformation. How is the financial performance of PT. Kereta Api Indonesia (PERSERO) Tbk studied included ratio analysis techniques such as liquidity, solvency and profitability ratios. Quantitative descriptive is the statistical analysis method used. The results of this study indicate that the current ratio has liquid criteria, while the quick ratio does not match the current ratio liquidity criteria. In terms of debt to asset ratio solvency standards, the company PT. Kereta Api Indonesia (PERSERO) Tbk has a solvable standard, while debt to equity ratio has a non solvable standard. Then, in terms of profitability, return on assetshas generally less effective criteria compared to return on equity which has effective criteria. The results of this study can be concluded that PT. Kereta Api Indonesia (PERSERO) Tbk is considered not ready to implement an economic and business growth program based on technological and digital innovation due to the condition of PT. Kereta Api Indonesia (PERSERO) Tbk which is not healthy. However, this can enable this company to be better, if PT. Kereta Api Indonesia (PERSERO) Tbk improved its company's performance, especially on debt to asset equity and return on assets.